Diagnóstico de falha em um cilindro vibrador de varetas de uma colhedora de café - Silva, Carlos Ademir da (2019)
Coffee harvesters operate with a vibration system to promote fruit spilling. The vibration system is usually coupled to the end of an axis, denominated a rod vibrating cylinder. This cylinder can fail in the field, which generally occurs due to fracture in the contour of the rod cylinder, with an angle of approximately 45º. This type of failure in the field occurs in a short period, from approximately 1669 hours to 2496 hours of constant work, 8 hours per day, which requires a failure diagnosis. In this sense, this work has as the primary objective of diagnosing fails in a rod vibrating cylinder of a coffee harvester. For this, we first mapped the fracture, and, subsequently, developed samples to perform non-destructive and destructive mechanical tests. These tests showed welding issues between the rod cylinder and the larger flange, to which the rod cylinder vibration system is coupled. In addition to presenting a thin wall of material with a thickness of only 10 mm, during the production process, the cylinder is machined to facilitate the assembly of the vibration system. The larger flange is thicker than the rod cylinder (35 mm), which makes the welding process more difficult, and defects may arise as a result. In view of the incidence of defects from the material of the vibrating tube, we suggested working with a prototype, to preserve the farmer's harvester. Therefore, we designed a prototype of the harvester in a reduced scale of 3:1, which was instrumented using an unidirectional strain gauges and an accelerometer to collect information on the vibration and tension concentration in the evaluated region of the cylinder, using a frequency inverter to perform the exact vibrations that occur in the vibrating cylinder of the production harvester. The prototype data allowed us to diagnose and prevent fails in the rod cylinder, as well as to validate numerical simulations via the Finite Element Method. Based on the results obtained in the laboratory analysis, such as the tube casting defects, the welding procedure is incorrect, with the entire set having been subjected to cyclic vibrations, consequently favoring the propagation of cracks in the rod vibrating cylinder. The results of the extensometry showed that the stresses were almost equal, with few variations, when compared to the numerical simulation. Due to a range of defects, we conclude that they were what caused the rod vibrating cylinder to fail. To avoid this, we suggest a Welding Procedure Qualification Record and Welding Process Specification to improve the manufacturing process of the rod vibrating cylinder and not compromise the harvester's useful life.